Effect of Irrigation Threshold on Crop Performances in Wet Seeded Rice - Parveen, S; Humphreys, E; Ahmed, M (Bangladesh Rice Journal, 2019)
Decreasing availability and increasing costs of water and labour are driving researchers and farmers to find management strategies that increase input water productivity and reduce labour requirement in rice production. Wet seeding instead of transplanting greatly reduces the labour requirement for crop establishment, whereas use of alternate wetting and drying (AWD) instead of continuous flooding reduces irrigation input. However, the safe threshold for irrigating wet seeded rice (WSR), and how this varies with growth stage, has not been established. Therefore, a greenhouse experiment was conducted to determine the effects of different degrees of irrigation threshold during different crop growth stages on crop performance of WSR. This was done in greenhouse experiment in the 2011 wet season at the International Rice Research Institute, Los Baños, Philippines. In the experiments, water stresses were applied by withholding irrigation until soil water tension increased to 10, 20 or 40 kPa at 10 cm below the soil surface. Soil water tension was measured using 30 cm long gauge tensiometer installed with the center of the ceramic cup. The stresses were applied during three crop stages: 3-leaf (3L) to panicle initiation (PI), PI to flowering (FL), and FL to physiological maturity (PM). The experiment was also included a continuously flooded (CF) treatment. Stress during 3L to PI increased the time to PI (by 2 to 4 days) but reduced the duration of grain filling by 3 to 5 days, the larger values with 20 and 40 kPa thresholds. There was no effect of stress thresholds of 10 to 40 kPa during PI-FL on crop duration. Stress during grain filling reduced the duration of grain filling by 6 days for all thresholds. Stresses of 20 and 40 kPa during 3L to PI reduced green leaf and tiller density at PI, but this effect disappeared with the imposition of CF after PI. There were consistent trends for lower final biomass as the level of water deficit stress increased, and imposition of stresses of 20 and 40 kPa at any or all three stages significantly reduced biomass compared with CF. These results suggest that, for shortening the ripening period, water stress may be imposed as 10 to 20 kPa during FL to PM. Bangladesh Rice j. 2018, 22(1): 73-81